Fe₃O₄/Ag/Bi₂ MoO₆ photoactivatable nanozyme for self-replenishing and sustainable cascaded nanocatalytic cancer therapy - Cao, Changyu (2022)
Catalytic cancer therapy based on nanozymes has recently attracted much interest. However, the types of the current nanozymes are limited and their efficiency is usually compromised and not sustainable in the tumor microenvironment (TME). Therefore, combination therapy involving additional therapeutics is often necessary and the resulting complication may jeopardize the practical feasibility. Herein, an unprecedented "all-in-one" Fe3 O4 /Ag/Bi2 MoO6 nanoparticle (FAB NP) is rationally devised to achieve synergistic chemodynamic, photodynamic, photothermal therapy with guidance by magnetic resonance, photoacoustic, and photothermal imaging. Based on its manifold nanozyme activities (mimicking peroxidase, catalase, superoxide dismutase, glutathione oxidase) and photodynamic property, cascaded nanocatalytic reactions are enabled and sustained in TME for outstanding therapeutic outcomes. The working mechanisms underlying the intraparticulate interactions, sustainability, and self-replenishment arising from the coupling between the nanocatalytic reactions and nanozyme activities are carefully revealed, providing new insights into the design of novel nanozymes for nanocatalytic therapy with high efficiency, good specificity, and low side effects.